The Role of Work Environment, Discipline, and Competence in Improving the Performance of Employees of the North Labuhanbatu Regency Education Office - Lubis, Ahmad Yasir; Harahap, Ihwan; Hasibuan, Abdul Rajis; Hapsari, Bahani Indah; Sihotang, Rolina; Rahayu, Sri (Journal of Finance and Business Digital, 2024)
The purpose of this study is to examine the effects of competency, work environment, and work discipline on the output of North Labuhanbatu Regency Education Office staff members. A survey with 100 respondents was used to gather data, and multiple linear regression was used for analysis. The study's findings indicate that these three factors significantly impact worker performance, with work discipline having the biggest impact, followed by competence and work environment. These three factors can account for the variance in employee performance, according to the determination coefficient (R2) of 65.2%. The recommendations produced are the need to improve work discipline, improve the work environment, and develop competencies to improve employee performance.